PEMODELAN SPASIAL BAHAYA LONGSOR DI DAS CILIWUNG HULU, KABUPATEN BOGOR - Muhamad Rizal Gojali; Boedi Tjahjono; Ernan Rustiadi (KOMPUTASI, 2020)
Landslide is a natural phenomenon that occurs because nature is looking for a balance due to disturbance affecting the land at the point of the landslide. Bogor Regency is categorized into a medium to high level ground vulnerable zone by BNPB, in this case the Cilwung Hulu watershed is an area that often experiences landslides. This study aims to develop a spatial model of landslides in the Ciliwung Hulu watershed using a PCA-based assessment method of the factors causing landslides. The results showed that there are seven parameters that can be used for spatial modeling of landslides, namely landform, land use, slope, rainfall, straightness, soil type, and lithology. Based on the results of the analysis it was found that the weight of each parameter is 0.347; 0.223; 0,200; 0,100; 0.071; 0.049; and 0.010. In this case landform has the highest weight as a determinant of landslide hazards. The area of landslide hazard class (low, medium, and high) obtained from the results of modeling are 4,651.53 ha (31%), 6,637.72 ha (43%), and 3,941.41 ha (26%) with accuracy overall of 57.8.